Teoria ewolucyjna firmy - Karaś, Mirosław (The Evolutionary Theory of the Firm, 2008)
The paper presents the evolutionary theory of the firm as one of lastly emerging among partial theories of the firm. The author points to the strong relation between this theory and the evolutionary economy as well as to the importance of routines in this theory.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 9-17